Item analysis test of science, Indonesian language, and mathematics using the rasch model in elementary schools - Ernawati, Ernawati; Habibah, Rini Yaumi; Syarifah, Nur; Firmansyah, Firmansyah; Attamimi, Has'ad Rahman (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2024)
Assessment of learning outcomes is an important component in the learning process to measure student learning achievements and assist teachers in determining appropriate learning strategies. This study aims to evaluate the quality of test items and student ability levels in Science, Indonesian Language, and Mathematics subjects using the Rasch model. The evaluation includes item reliability, person reliability, and the overall fit of the test items to the model. The research was conducted with 187 students from four public elementary schools in West Jakarta, using a quantitative method with a descriptive design. Data collection involved administering tests to the students, which consisted of 12 items in Science, eight items in Indonesian Language, and 10 items in Mathematics. The data were analyzed using the Quest software to provide comprehensive Rasch analysis results. The findings revealed that the consistency of student responses was weak, but the quality of the test items was good, as evidenced by high item reliability and low person reliability. In terms of model fit, all Science items met the Rasch model criteria, while in the Indonesian Language, one item (item 19) did not fit, and in Mathematics, three items (items 21, 27, and 28) failed to meet the criteria. The analysis of item difficulty levels showed a predominance of medium difficulty. The validity results indicated that 26 items were valid, and four items (1 in Indonesian Language and 3 in Mathematics) were invalid. Most students fell into the medium ability category across all subjects, indicating the need for further tutoring and personalized learning strategies to improve student performance.